Intergenerational continuity in the political life of China - Tsay, K. A. (Journal of Oriental Studies, 2016)
Commitment to the continuity of generations and traditionalism by leadership of China is a fundamental principle of the development of state and creation a «society of small tranquility.» All of leaders in China are adherents of «socialism with Chinese characteristics», which indicates a close connection between the past experience and requirements of the modern world.